Determinasi Keputusan Pembelian Produk Pencuci Piring: Ditinjau berdasarkan Bauran Pemasaran Produk - Afrilliana, Nadia; Nurrahmi, Maftuhah; Hustia, Anggreany (Universitas muhammadiyah palembang, 2022)
Marketing Mix (Product, Distribution and Promotion) on purchasing decisions of dishwashing liquid products in North Indralaya District Ogan Ilir and to determine the effect of marketing mix partially on purchasing decisions for dishwashing liquid products in North Indralaya District Ogan IlirThe number of samples in as many as 96 respondents. The analytical techniques used are multiple linear regression analysis, F Test, T test and coefficient of determination (R2). The results of the F hypothesis test show that there is a significant influence on the marketing mix on purchasing decisions. While partially the Product (X1) has a significant effect on the purchase decision. Distribution Variables (X2) have a significant effect on purchasing decisions and promotions (X3) have a significant effect on purchasing decisions.